Effectiveness Of Educaplay Platform On Learning Results Of Civics Learning In Elementary School - Septianingsih, Mia Aris; Widyasari, Choiriyah (Universitas Pakuan, 2025)
This study aims to determine the effectiveness of the Educaplay platform in improving student learning outcomes in Civics subjects in elementary schools. The research used a quantitative method with a Quasi Experiment design, adopting a control group and experimental group design. The research subjects included classes 4B and 4D MIM PK Kartasura with a random sampling technique or simple random sampling. So that the sample of this study can be produced in grades 4B and 4D at MIM PK Kartasura with a population of 39 students and only uses a sample of 30 students, each of which is taken as a sample of 15 students. Class 4B was chosen as an experimental group that would get special treatment, namely learning using the Educaplay platform while class 4D as a control class that did not get special treatment. Data collection uses pre-test and post-test to measure students' Civics learning outcomes. Data analysis through the prerequisite test and hypothesis testing stages. The result of the study is that there is a difference between the control class and the experimental class, this is evidenced by the independent samples test which shows that the sig value is obtained. (2 tailed) of 0.001 0.05, it can be concluded that there is an average difference in students' Civics learning outcomes between using Ecucaplay platform media and non-digital media (lectures). So it can be said that Ho is rejected and Ha is accepted. Group statistical results also show that the average value of the experimental class results is 86, 33 while the control class is 75.33. It can be concluded that the learning outcomes in the experimental class that received special treatment using the educaplay platform were sufficient to affect learning outcomes in Civics subjects at MIM PK Kartasura. For the results of the effectiveness test with the calculation of n-gain shows the mean (average value) of the experimental class of 62.70 or 62% and it is stated that the use of educaplay platfrom media is quite effective on students' Civics learning outcomes. While the control class was 26.84 or 26% and declared ineffective in using lectures on Civics learning outcomes.